Pre-operative direct puncture embolization of head and neck hypervascular tumors using SQUID 12. Issue 3 (June 2020) - Pedicelli, Alessandro; Lozupone, Emilio; Valente, Iacopo; Snider, Francesco; Rigante, Mario; D'Argento, Francesco; Alexandre, Andrea; Garignano, Giuseppe; Chiumarulo, Luigi; Paludetti, Gaetano; Colosimo, Cesare
Objective: The authors have evaluated their experience in pre-operative direct puncture embolization of hypervascular tumors of the head and neck using SQUID 12, an embolic liquid agent. Methods: Between July 2016 and March 2019, the authors retrospectively reviewed clinical, embolization and surgical data of 11 consecutive patients with 12 hypervascular head and neck tumors who had undergone pre-operative embolization using SQUID 12. Percutaneous embolizations were performed by inserting a 19-22 Gauge needle directly into the tumor under ultrasound, fluoroscopic and/or endoscopic guidance. The hub of the needle was connected to a 15-cm DMSO-compatible extension tube, and the SQUID 12 was injected. Results: Total or near-total devascularization was achieved in 11 over 12 cases. Complete en-bloc tumor removal by surgery was achieved in all cases. Only one patient required blood transfusion. No major periprocedural adverse events were recorded. Conclusions: Direct puncture embolization of hypervascular tumors of the head and neck using SQUID 12 seems to be safe and effective. It may offer almost complete devascularization due to homogenous, deep penetration in the tumor, with optimal visibility of the agent throughout the percutaneous procedure. It may reduce intraoperative blood loss and the need for transfusion, thus facilitating complete surgical resection.